Pengaruh Dewan Komisaris, Dewan Direksi, Komite Audit Terhadap Nilai Perusahaan Subsektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Arthur Suwandono, Charles; Sunarto, Sunarto (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2025)
Growth of banking sector in Indonesia has highlighted the importance of implementing good governance to enhance firm value. Objective of this study is to investigate impact that good governance has practices firm value during the 2020– 2024 period. Additionally, firm size is included as a control variable to provide a more comprehensive evaluation of company value. Sampling was conducted purposively with reference to established qualifications focusing on banking sub-sector companies listed during the specified period and having complete financial statement data, resulting in 204 firm-year observations. Data analysis was conducted using multiple regression analysis. Findings reveal that both the board of commissioners and the audit committee have a significant negative effect on firm value, whereas the board of directors demonstrates a temporary yet significant positive influence. In contrast, firm size does not show statistically significant impact. The coefficient of determination (R²) is 10.6%, indicating that most variations in firm value are influence by external factors not included in the proposed design.